Redcoats to Tommies the experience of the British soldier from the eighteenth century - Linch, Kevin 1974-; Lord, Matthew 1992- (The Boydell Press, 2021)
This book surveys and examines the history of Britain's soldiers from the eighteenth to the twentieth century. It focuses on the lifecycle of a soldier, including enlistment and experience, and on identity, representations and place in society. It covers the diverse military forces of the British crown - the regular army, home defence forces, part-time soldiers, auxiliaries, officers, non-commissioned officers and rank and file - across times of conflictand peace and their wider relationship to families, communities, government and society. Additionally, it considers both British troops, and, recognising Britain's soldiers as a transnational phenomenon, forces raised outside ofBritain and Ireland. By assessing the evolution of Britain's soldiers across three centuries, the book highlights continuity and change and gauges how far the basic fundamentals, principles and priorities of army life have endured or been transformed during the existence of a continual standing army. The book includes up-to-date research from a new generation of early-career researchers and reflections from established scholars